HerMES: Herschel-SPIRE observations of Lyman break galaxies - Rigopoulou, D.; Magdis, G.; Ivison, R.; Amblard, A.; Arumugam, V.; Aussel, H.; Blain, A.; Bock, J.; Boselli, A.; Buat, V.; Burgarella, D.; Castro-Rodríguez, N.; et al. (Wiley-Blackwell Publishing Ltd., 2010)
We present first results of a study of the submillimetre (submm) (rest-frame far-infrared) properties of z ~ 3 Lyman break galaxies (LBGs) and their lower redshift counterparts BX/BM galaxies, based on Herschel-SPIRE observations of the Northern field of the Great Observatories Origins Deep Survey (GOODS-N). We use stacking analysis to determine the properties of LBGs well below the current limit of the survey. Although LBGs are not detected individually, stacking the infrared luminous LBGs (those detected with Spitzer at 24 |xm) yields a statistically significant submm detection with mean flux <S250> = 5.9 ±1.4 mJy confirming the power of SPIRE in detecting UV-selected high-redshift galaxies at submm wavelengths. In comparison, the Spitzer 24 |j.m detected BX/BM galaxies appear fainter with a stacked value of <S250> = 2.7 ± 0.8 mJy. By fitting the spectral energy distributions (SEDs) we derive median infrared luminosities, LIR, of 2.8 × 1012 L? and 1.5 × 1011 L. for z ~ 3 LBGs and BX/BMs, respectively. We find that LIR estimates derived from present measurements are in good agreement with those based on UV data for z ~ 2 BX/BM galaxies, unlike the case for z ~ 3 infrared luminous LBGs where the UV underestimates the true LIR. Although sample selection effects may influence this result we suggest that differences in physical properties (such as morphologies, dust distribution and extent of star-forming regions) between z ~ 3 LBGs and z ~ 2 BX/BMs may also play a significant role. © 2010 The Authors. Journal compilation © 2010 RAS.